Stability and accuracy of steady-state motions in loaded copying system: analytical approach - Halanay, Andrei; Safta, Carmen A. (Computer Assisted Methods in Engineering and Science, 1999)
An analytical study of stability is made for a hydromechanical servomechanism used in copying systems. In the framework of a nonlinear system of ODE mathematically modelling the servomechanism, we prove that for a ramp input the steady-state solution bifurcates into a stable limit cycle for a certain value of the underlap spool valve